2019
DOI: 10.11152/mu-1764
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative difficult airway prediction using suprahyoid and infrahyoid ultrasonography derived measurements in anesthesiology

Abstract: Airway management is one of the most important skills in everyday practice of anesthesia. Improper airway management might contribute to significant morbidity and mortality. In some patients, clinical parameters do not anticipate all difficulties related to airway management. Ultrasonography (US) might confer a potential screening tool for difficult airway. Suprahyoid and infrahyoid US measurements have been investigated for difficult airway prediction in anesthesiology. The most extensively investigated param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
17
0
4
Order By: Relevance
“…The investigator can easily identify the bright hyperechoic structures: the mandible and the hyoid bone. HMD is measured between the anterior border of the chin and the anterior border of the hyoid [17]. In the study by Petrisor et al [18], HMDR seemed to have superior diagnostic accuracy with a cut-off value of 1.23 provides 100% (39.8-100.0) sensitivity and 90.5% (69.6-98.8) speci city for the prediction of di cult airway in the obese population.…”
Section: Discussionmentioning
confidence: 97%
“…The investigator can easily identify the bright hyperechoic structures: the mandible and the hyoid bone. HMD is measured between the anterior border of the chin and the anterior border of the hyoid [17]. In the study by Petrisor et al [18], HMDR seemed to have superior diagnostic accuracy with a cut-off value of 1.23 provides 100% (39.8-100.0) sensitivity and 90.5% (69.6-98.8) speci city for the prediction of di cult airway in the obese population.…”
Section: Discussionmentioning
confidence: 97%
“…All ultrasound measurements were performed by a single researcher after positioning patients supine with head and neck in neutral position. A low frequency probe was placed on patient's neck perpendicular to skin to measure hyomental distance [8] (Figure 1). The researcher adjusted the ventilation according to the appropriate parameters for each patient.…”
Section: Ultrasonographic Measurementmentioning
confidence: 99%
“…A previous study demonstrated that one of upper airway anatomy parameters of hyomental distance, the distance between hyoid bone and tip of the chin, may considered a predictor for LMA size choice [8]. As such, we designed a prospective, randomised controlled study to compare the e cacy of weight-based method to hyomental distance-based method for individualized estimation of LMA size selection in breast cancer surgery patients.…”
Section: Introductionmentioning
confidence: 99%
“…When measured, the patient should be asked to lie supine and put the head in a neutral position. Generally, a 6-13 MHz high-frequency ultrasonic transducer is used for ultrasonic scanning (22,23). The linear ultrasonic probe is placed vertically on the larynx to measure the vertical distance between the skin and six different anatomical sites.…”
Section: Thickness Of Anterior Neck Soft Tissuementioning
confidence: 99%